Experiments in the purification and characterization of enzymes : a laboratory manual / Thomas E. Crowley, Department of Mathematics and Natural Sciences, National University, La Jolla, California, Jack Kyte, Department of Chemistry, University of California, San Diego, La Jolla, California. - Crowley, Thomas E.; Kyte, Jack
"Experiments in the Purification and Characterization of Enzymes: A Laboratory Manual provides students with a working knowledge of the fundamental and advanced techniques of experimental biochemistry. Included are instructions and experiments that involve purification and characterization of enzymes from various source materials, giving students excellent experience in kinetics analysis and data analysis. Additionally, this lab manual covers how to evaluate and effectively use scientific data. By focusing on the relationship between structure and function in enzymes, Experiments in the Purification and Characterization of Enzymes: A Laboratory Manual provides a strong research foundation for students enrolled in a biochemistry lab course by outlining how to evaluate and effectively use scientific data in addition to offering students a more hands-on approach with exercises that encourage them to think deeply about the content and to design their own experiments. Instructors will find this book useful because the modular nature of the lab exercises allows them to apply the exercises to any set of proteins and incorporate the exercises into their courses as they see fit, allowing for greater flexibility in the use of the material. Written in a logical, easy-to-understand manner, Experiments in the Purification and Characterization of Enzymes: A Laboratory Manual is an indispensable resource for both students and instructors in the fields of biochemistry, molecular biology, chemistry, pharmaceutical chemistry, and related molecular life sciences such as cell biology, neurosciences, and genetics. Offers project lab formats for students that closely simulate original research projects. Provides instructional guidance for students to design their own experiments . Includes advanced analytical techniques. Contains adaptable modular exercises that allow for the study proteins other than FNR, LuxG and LDH. Includes access to a website with additional resources for instructors"--Page 4 of cover.
Includes bibliographical references (pages 227-231) and index.
Keywords: Enzymes -- Laboratory manuals; Enzymes -- Laboratory Manuals; Enzymes -- Laboratory Manuals